Evaluation of Parking Areas in Ramadi CBD - Sh.Mahmmod, Thaer (Anbar Journal of Engineering Sciences, 2011)
The car parking problem in Ramadi CBD Area is considered the important urban problems that the Ramadi city suffer especially in the CBD area. Traffic problems are the main challenge of the CBD areas which has direct relationship related to the city commercial use. The CBD main streets were chosen as a case study and the parking area on them were surveyed. The study explained that there is a sharp lack in the parking areas especially in the districts no. 4, 6, 7, and 9. The parking in the surveyed area are of on-street type. In this study there is number of conclusions, recommendations and suggestions for the short and long term projects related to this issue to put plans for solving this urban problem in Ra-madi CBD.